Synthesis of membrane-type graphene oxide immobilized manganese dioxide adsorbent and its adsorption behavior for lithium ion. (September 2021) - Cheng, Mengmeng; Yao, Chenxue; Su, Yan; Liu, Jinglei; Xu, Lijian; Hou, Shifeng
Abstract: Recently, there has been an urgent need to develop new materials and technologies for extracting lithium ions. Herein, the membrane-type adsorbent of manganese dioxide (MnO2 ) is prepared by a vacuum filtration method using graphene oxide (GO) as a binder and amino-β-cyclodextrin (amino-β-CD) as an adjuvant. The results of thermogravimetric analysis show that MnO2 is successfully immobilized on GO layers with a content of about 24 wt%, which enabled rapid adsorb lithium ions from the ionic solution. In addition, the permeation experiment shows the membrane has specific selectivity for lithium ion transport and adsorption, which is manifested in the selectivity ratios of K + /Li +, Na + /Li + and K + /Na + to 2.5, 3.2 and 0.8, respectively. Adsorption experiments show that GO-β-CD/MnO2 membrane has a high adsorption capacity for lithium ions (37.5 mg g −1 ). The adsorption kinetic curve indicates that the lithium adsorption process is controlled by the chemical adsorption mechanism. In the enrichment experiment, the concentration of lithium ions from seawater can be enriched to 1.2 mg L −1 after 100 cycles. The results suggest that the developed GO-β-CD/MnO2 membrane could effectively extract lithium ions from seawater. Highlights: A membrane-type Li + adsorbent is synthesized based on MnO2 . Selectivity ratios of K + /Li +, Na + /Li + and K + /Na + to 2.5, 3.2 and 0.8. Adsorption capacity for lithium ions is 37.5 mg g −1 . Enrichment concentration of Li + from seawater can reach 1.2 mg L −1 .